Optimal Integration of Solar Assisted Heating Systems in Residential Buildings - Igor Shesho; Risto Filkoski; Done Tashevski; Monika Uler-Zefikj (Energija, Ekonomija, Ekologija)
The decrease in conventional energy resources, environmental pollution issues and climate change are the leading factors inducing the increase of energy efficiency criteria. Trends to improve energy efficiency are mainly aimed at the construction sector as one of the leading sectors in energy consumption. In the paper the performance of the decentralized solar assisted heating systems (SAHS) for climatic conditions in Macedonia was analysed in order to assess its possibility to be integrated as part of the district heating system. The analysis is based on a holistic approach, in which the performance of the SAHS is generally functionally dependent on four factors: (1) the characteristics of each component, (2) the system structure and mutual interactions of the components, (3) the management method and (4) specific energy consumption for heating of the building. The specific analysis is directed toward the assessment of the solar fraction of the SAHS as a function of the building energy performance and system heating temperature range. The numerical modelling of the processes occurring in systems was performed with the dynamic simulation software TRNSYS. Both dynamic models of the solar bivalent system and reference building were developed. The dynamic model contributes to the flexibility of conducting parametric analysis. The obtained results from the parametric analysis were condensed in a general table upon which the analysis of system performance was performed